Aflatoxin exposure assessed by aflatoxin albumin adduct biomarker in populations from six African countries: REVIEW ARTICLE - Xu, Y. (World Mycotoxin J, 2018)
Aflatoxins are a group of carcinogenic mycotoxins that have been implicated to have other adverse health impacts, including child growth impairment and immune function suppression. Aflatoxin B(1) is the most toxic and most common of the aflatoxins. Contamination of various food crops is common in sub-Saharan Africa, particularly in staple crops such as maize and groundnuts, leading to chronic dietary exposure in many populations. For many years we have used the aflatoxin albumin adduct as a biomarker of aflatoxin exposure, assessed using a competitive inhibition enzyme linked immunosorbent assay (ELISA). Here, we review our recent studies of human exposure in six African countries; Gambia, Guinea, Kenya, Senegal, Tanzania and Uganda. This data shows the widespread exposure of vulnerable populations to aflatoxin. Geometric mean (95% confidence interval) levels of the biomarker ranged from 9.7 pg/mg (8.2, 11.5) in Ugandan children to 578.5 pg/mg (461.4, 717.6) in Kenyan adolescents during an acute aflatoxicosis outbreak year. We describe how various factors may have influenced the variation in aflatoxin exposure in our studies. Together, these studies highlight the urgent need for measures to reduce the burden of aflatoxin exposure in sub-Saharan Africa.